Reinterpretasi Konsep Nusyūz Dan Penyelesaiannya Dalam Kompilasi Hukum Islam: Tinjauan Kritis Perspektif Mubādalah - Muhammad Dhiyaulhaq Syahrial Ramadhan; Ahmad In’am Awaluddin (Muhammadiyah University of Surabaya, 2025)
This study aims to analyze gender bias in the regulation of nusyūz in the Compilation of Islamic Law (KHI) and formulate a reinterpretation based on the principle of reciprocity (mubādalah). This study examines the concept of nusyūz in the Compilation of Islamic Law (KHI) which is considered to be still gender-biased because it only regulates nusyūz on the wife's side without accommodating the possibility of nusyūz on the husband's side. In fact, the Qur'an in QS. An-Nisa' verses 34 and 128 explicitly admit that nusyūz can be done by both sides. Using a qualitative research method with a literature approach, this study analyzes the KHI articles on nusyūz (Articles 80, 83, 84, and 152) through the perspective of the mubādalah theory developed by Faqihuddin Abdul Kodir. The theory of mubādalah emphasizes the principles of reciprocity, equality, and partnership in the relationship between husband and wife as stated in QS. Ar-Rum: 21 and the Hadith of Mu'adz bin Jabal. The results of the study show that the regulation of nusyūz in KHI is contrary to the principle of reciprocity because: (1) it only burdens the wife without parallel sanctions for the husband; (2) providing disproportionate legal consequences in the form of the loss of the wife's rights; (3) does not regulate a constructive conflict resolution mechanism; and (4) using the phrase